Peningkatan Ketepatan Hafalan melalui Penguatan Program Tahfidz Santri Khotimat di Pondok Pesantren An-Nur 2 Al-Murtadlo - Ramadhanti Syifa Salsabila; Ramadhanti Syifa Salsabila (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Memorizing the Quran is an important Islamic tradition aimed at preserving the authenticity of revelation and fostering a generation of noble character. However, the implementation of the tahfidz program often faces challenges, particularly regarding memorization accuracy and consistency of muroja’ah (recitation). This Community Service Program (PKM) activity aims to strengthen tahfidz development through an individualized approach, intensive mentoring, and the creation of a conducive religious environment. Results show an increase in memorization accuracy, muroja’ah discipline, and self-confidence among students who are khotimat (instructors). Continuous evaluation and a structured coaching model have proven effective in supporting the success of the tahfidz program.